(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this present paper, simple and accurate algorithm was established for the solution ofgeneralized Barker’s equation of parabolic orbital motion.The algorithm based on the continued fractionexpansion theory. Numerical applications of the algorithm are alsogiven.